ROLE OF RELATIONSHIP MARKETING IN INTEGRATING A NEW PRODUCT INTO AN INDUSTRIAL BRAND - RAHMAN, MUHIB NOOR (2014)
Relationship Marketing and Industrial Brand Management are two distinctively different field of research in marketing. The two fields however, exerts significant influence for products in industrial market. Effective relationship marketing process results in a set of desirable relationship outcome mediated through relationship variables. The outcomes impact buyers’ perception heavily for the industrial market. On the other hand customers’ perception and buying decision is also heavily influenced by suppliers brand image. This link is being tested in the following study in the context of a new product launch in industrial markets.